2013
DOI: 10.1089/neu.2012.2614
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 Expression in Post-Traumatic Syringomyelia

Abstract: Aquaporin-4 (AQP4) is an astroglial water channel protein that plays an important role in the transmembrane movement of water within the central nervous system. AQP4 has been implicated in numerous pathological conditions involving abnormal fluid accumulation, including spinal cord edema following traumatic injury. AQP4 has not been studied in posttraumatic syringomyelia, a condition that cannot be completely explained by current theories of cerebrospinal fluid dynamics. Alterations of AQP4 expression or funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Oshio et al found that AQP4 was intensely stained throughout the gray matter in spinal cord, especially in the capillary-surrounding astrocytic end-feet 19 . In particular, AQP4 and spinal cord edema are positively correlated 40,41 . AQP4 in spinal cord is expressed in glial cells throughout the gray matter and glial foot processes adjacent to the spinal capillary endothelium 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Oshio et al found that AQP4 was intensely stained throughout the gray matter in spinal cord, especially in the capillary-surrounding astrocytic end-feet 19 . In particular, AQP4 and spinal cord edema are positively correlated 40,41 . AQP4 in spinal cord is expressed in glial cells throughout the gray matter and glial foot processes adjacent to the spinal capillary endothelium 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Spinal cord trauma initiates a severe and prolonged inflammatory response [21][22][23][24] with destruction of the spinal cord tissue surrounding the site of injury and causing a gradual expansion of the cavity of injury (COI) [18,35,40]. Phagocytic macrophages loaded with luxol fast blue-positive myelin granules have been observed in SCI lesions beyond 8 weeks post-injury [21] and are considered central mediators of this destructive inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages continue to phagocytize myelin, persisting for more than 8 weeks post-spinal cord injury (SCI) [21]. As this inflammatory, phagocytic macrophage infiltrate persists, the cavity of injury (COI) increases in volume [18,35,40] creating a barrier for axonal regeneration [20], while the surrounding spinal cord tissue is irreversibly destroyed. Based on these histopathological findings we have postulated that a reduction in the numbers of macrophages in the COI by pharmacological treatments has the potential to protect the nervous system, a therapy designed to limit tissue destruction and potentially reduce neurological deficits.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Hemley et al [93] has shown a relation between the increase of astrocytic AQP4 expression and the persistence of syrinxes in a rat model of posttraumatic syringomyelia where a significant up-regulation of AQP4 was observed at three and six weeks post injury at the level of the syrinx and in adjacent rostral and caudal levels.…”
Section: Aqp Expression In Disease Conditions Of Spinal Cordmentioning
confidence: 99%